Short-Term Forecasting of the Freight Turnover of Organizations taking into account Regional Differences - TSYRENOV, Dashi Dashanimaevich; RUBAN, Vladimir Alekseevich; KHAYKHADAEVA, Oktyabrina Dmitrievna; VANCHIKOVA, Elena Nikolaevna; MUNKUEVA, Irina Sergeevna (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
The purpose of the paper is to improve the methods of short-term forecasting of the value of the freight turnover of organizations taking into account differentiation of the subjects of the Russian Federation. The forecast is compiled for the specified groups of regions obtained by analyzing the contingency of the subjects of the Russian Federation with respect to the value of the freight turnover and the conditions of its formation, followed by the statistical discrimination. The described technique improves the accuracy of predictive estimates and confirms the influence of structural differences in the socio-economic development of regions on the freight turnover value.